TRANSCODING BETWEEN HYPER-ANTAGONISTIC MILIEUS: STUDIES ON THE CROSS-PLATFORM RELATIONS BETWEEN RADICAL POLITICAL WEB SUBCULTURES - Hagen, Sal; Tuters, Marc; Peeters, Stijn; De Keulenaar, Emillie; Wilson, Jack; Willaert, Tom (AoIR Selected Papers of Internet Research, 2020)
This panel brings together research into the cross-platform relations between radical Web subcultures and how they are constitutive of “hyper-antagonistic” politics in broader Web discourses. The papers share a concern with vernacular practices of “fringe” platforms favoured by an insurgent far-right movement and their relations to more “mainstream” social media. They engage with the concept of “transcoding between milieus” (Deleuze & Guattari 1987, 322) as a means to empirically describe multiple transversal processes across different strata of the Web in which “one milieu serves as the basis for another” (313). All papers ground their conceptual analysis in data-driven empirical approaches using historical datasets ranging from “mainstream” platforms like YouTube, to more “fringe” spaces like 4chan. The papers furthermore all use 4chan’s far-right /pol/ board as a reference point for a vernacular “hyper-antagonistic” style that emerged out of this period – a style that has often been related to the “alt-right”. Together, the four papers in this panel offer insights into the apparent insurgency of far-right subcultures within broader online discourse in the Anglo-American context over the course of the last half decade. Each does so with a particular focus, ranging from subcultural conflict between Tumblr and 4chan, the transcoding of the “Kekistan” meme between 4chan and YouTube, the emergence of far-right vernacular in the comments of Breitbart News, and the robustness of hyper-antagonistic discourse after deplatforming measures.